2010
DOI: 10.3389/fpsyg.2010.00030
|View full text |Cite
|
Sign up to set email alerts
|

Congruency between word position and meaning is caused by task Induced spatial attention

Abstract: We report an experiment that compared two explanations for the effect of congruency between a word's on screen spatial position and its meaning. On one account, congruency is explained by the match between position and a mental simulation of meaning. Alternatively, congruency is explained by the polarity alignment principle. To distinguish between these accounts we presented the same object names (e.g., shark, helicopter) in a sky decision task or an ocean decision task, such that response polarity and typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
82
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(89 citation statements)
references
References 21 publications
5
82
2
Order By: Relevance
“…Polarity differences have often been discussed as an alternative explanation for metaphor congruency effects (e.g., Pecher, Van Dantzig, Boot, Zanolie, & Huber, 2010;Schubert, 2005;Ulrich & Maienborn, 2010;Vallesi et al, 2008;Van Dantzig, Zeelenberg, & Pecher, 2009;Weger & Pratt, 2008), but whether polarity differences can explain previously observed metaphor congruency effects has never been examined. Given that most studies have examined how concepts are structured in vertical space (see Landau, Meier, & Keefer, 2010), this article examines the mechanisms through which the vertical position of stimuli influence the speed with which abstract bi-polar concepts are categorized.…”
Section: Polarity Differences Vs Interference Effectsmentioning
confidence: 99%
“…Polarity differences have often been discussed as an alternative explanation for metaphor congruency effects (e.g., Pecher, Van Dantzig, Boot, Zanolie, & Huber, 2010;Schubert, 2005;Ulrich & Maienborn, 2010;Vallesi et al, 2008;Van Dantzig, Zeelenberg, & Pecher, 2009;Weger & Pratt, 2008), but whether polarity differences can explain previously observed metaphor congruency effects has never been examined. Given that most studies have examined how concepts are structured in vertical space (see Landau, Meier, & Keefer, 2010), this article examines the mechanisms through which the vertical position of stimuli influence the speed with which abstract bi-polar concepts are categorized.…”
Section: Polarity Differences Vs Interference Effectsmentioning
confidence: 99%
“…Of relevance to the current inquiry, the precise mechanism supporting word verticality mappings remains a matter of debate (see Pecher, van Dantzig, Boot, Zanolie, & Huber, 2010). Most commonly, it has been suggested that retrieving the meaning of object, valence, and power words may activate spatial representations that either conflict or converge with those elicited by different screen positions (Schubert, 2005;Meier & Robinson, 2004;Zwaan & Yaxley, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…1 flying/non-flying; Exp. 2 living/nonliving) was faster when the words were presented in a spatially compatible location (e.g., flying animal in the top half of the screen) (cf., Pecher, Van Dantzig, Boot, Zanolie, & Huber, 2010). Estes et al (2008) first reported that even when word meaning is task-irrelevant, implicit location words (e.g., hat, shoe) still serve as spatial cues for involuntary attentional orientation.…”
Section: Introductionmentioning
confidence: 99%